Obâzannost' naslednikov vozmestit' zatraty na soderžanie, uhod, lečenie i pogrebenie nasledodatelâ i pravopreemstvo : sootnošenie ponâtij - Râbokon', Èvgenij Aleksandrovič (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
Abstract Duties of heirs on the compensation of expenses on the maintenance, care, treatment and burial of the deceased, indicated in an item 1232 of the Civil code of Ukraine 2003, did not belong to the deceased personally, and that is why are not the object of inherited succession. At the same time these duties are expediently attributed to composition of inheritance, that draws distribution on them norms of the inherited legislation, in particular, part 1 of item 1282 of the Civil code of Ukraine in relation to limitation of responsibility of heirs by the cost of the inherited property. Providing with the certain duties of heirs, but not other persons (family members or relatives of the deceased), is indissolubly constrained and contingently a grant to them legal status of heirs, by inalienable part of that and such duties become. The simultaneous coexistence of duties of heirs tocompensate the charges, envisaged in an item 1232 of the Civil code of Ukraine, and not including last in the complement of inheritance (inherited passive), is therefore impossible
Keywords: succession; inheritance law; heirs’ obligations; deceased; inherited passive